Adenosine A(2A) receptor blockade reverts hippocampal stress-induced deficits and restores corticosterone circadian oscillation - Batalha, V. L. (2013)
Maternal separation (MS) is an early life stress model that induces permanent changes in the central nervous system, impairing hippocampal long-term potentiation (LTP) and spatial working memory. There are compelling evidences for a role of hippocampal adenosine A(2A) receptors in stress-induced modifications related to cognition, thus opening a potential window for therapeutic intervention. Here, we submitted rats to MS and evaluated the long-lasting molecular, electrophysiological and behavioral impairments in adulthood. We then assessed the therapeutic potential of KW6002, a blocker of A(2A) receptors, in stress-impaired animals. We report that the blockade of A(2A) receptors was efficient in reverting the behavior, electrophysiological and morphological impairments induced by MS. In addition, this effect is associated with restoration of the hypothalamic-pituitary-adrenal axis (HPA-axis) activity, as both the plasma corticosterone levels and hippocampal glucocorticoid receptor expression pattern returned to physiological-like status after the treatment. These results reveal the involvement of A(2A) receptors in the stress-associated impairments and directly in the stress response system by showing that the dysfunction of the HPA-axis as well as the long-lasting synaptic and behavioral effects of MS can be reverted by targeting adenosine A(2A) receptors. These findings provide a novel evidence for the use of adenosine A(2A) receptor antagonists as potential therapy against psychopathologies